KONTRIBUSI SEKTOR PERTANIAN PADI DALAM UPAYA MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA LONAM KECAMATAN PEMANGKAT DALAM PERSFEKTIF EKONOMI ISLAM - Astuti, Wenti (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This research is motivated by the potential of extensive land and fertile soil in Lonam Village, Pemangkat District, which has not yet been fully maximized to contribute to improving the local economy. Islam encourages food security through its Sharia, specifically through zakat, which involves those with surplus wealth giving some of it to those in need, once they reach nisab and haul. The theories used in this research are: 1) the theory of contribution, and 2) the theory of agriculture. This research employs a descriptive qualitative approach and is categorized as field research. Data collection techniques used include observation, interviews, and documentation. Data sources consist of primary data from rice farmers in Lonam Village and secondary data from the Central Statistics Agency and the Agriculture Department. The data analysis techniques include data reduction, data presentation, and final stage analysis. The data validity technique used is triangulation. The research concludes that the contribution of the rice agriculture sector is significant to the community, as evidenced by the annual increase in harvest yields and government assistance provided to farmers. Increased harvests can boost the purchasing power within the community, allowing people to meet their daily needs. From an Islamic economic perspective, improving the economy can be achieved through zakat mal that has reached the nisab, thereby assisting the less fortunate who are eligible to receive it.